2022
DOI: 10.3390/nano12040707
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Relaxation Behavior of a Mononuclear Co(II) Complex Featuring Long Axial Co-O Bond

Abstract: Co(II) mononuclear complex with different coordination geometry would display various of field-induced single-ion magnet (SIM) behaviors. Here, we identify a field-induced single-ion magnet in a mononuclear complex Co(H2DPA)2·H2O (H2DPA = 2,6-pyridine-dicarboxylic acid) by the hydrothermal method. The long axial Co-O coordination bond (Co1‧‧‧O3) can be formed by Co1 and O3. Therefore, Co(II) ion is six-coordinated in a distorted elongated octahedron. AC magnetization susceptibilities show that the effective en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The incorporation of appropriate impurity ions into host lattices has been exploited as a promising method to stabilize the crystallographic phases while modulating the optical, electronic, and magnetic properties of diverse semiconductors [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Regarding the halide perovskites, the partial substitution of Pb 2+ by divalent metal ions, such as Cu 2+ , Mg 2+ , Fe 2+ , Co 2+ , Ni 2+ , and Mn 2+ at the B sites of the perovskite lattice have been demonstrated [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Klug et al revealed that the perovskite films retain an excellent photovoltaic performance if less than 3% Pb 2+ ions are substituted by homovalent metal species due to the high tolerance of the perovskite lattices [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of appropriate impurity ions into host lattices has been exploited as a promising method to stabilize the crystallographic phases while modulating the optical, electronic, and magnetic properties of diverse semiconductors [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Regarding the halide perovskites, the partial substitution of Pb 2+ by divalent metal ions, such as Cu 2+ , Mg 2+ , Fe 2+ , Co 2+ , Ni 2+ , and Mn 2+ at the B sites of the perovskite lattice have been demonstrated [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Klug et al revealed that the perovskite films retain an excellent photovoltaic performance if less than 3% Pb 2+ ions are substituted by homovalent metal species due to the high tolerance of the perovskite lattices [ 31 ].…”
Section: Introductionmentioning
confidence: 99%